A supported catalyst and its preparation method and its application in direct low-temperature conversion of methane to produce acetic acid

By loading metal single atom active components on molecular sieve or C3N4 support, a high stability single atom catalyst was prepared, which solved the problems of high cost, low selectivity and poor cycle stability in the direct conversion of methane to acetic acid technology, and achieved Low temperature and high efficiency methane conversion to acetic acid reaction meets the requirements of green chemistry.

CN116265110BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111543742.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2025-01-17
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

The existing methane direct conversion of acetic acid technology has the problems of high catalyst cost, low selectivity, poor cycle stability and unclear reaction mechanism, which is difficult to meet the future production needs of "green chemistry".

Method used

Use a supported catalyst, including metal single atom active components (such as copper, nickel, chromium, iron) and molecular sieve or C3N4 as support, and prepares through equal volume impregnation method, combining acid treatment and calcination steps to form a high-stability single atom catalyst. , and the reaction of methane and CO was carried out under low temperature conditions.

Benefits of technology

It achieves high selectivity (up to 90%) of direct conversion of methane to acetic acid at low temperature, reduces reaction energy consumption and cost, conforms to the concept of "green chemistry", and has good cycle stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003415187990000121
    Figure BDA0003415187990000121
  • Figure BDA0003415187990000122
    Figure BDA0003415187990000122
  • Figure BDA0003415187990000131
    Figure BDA0003415187990000131
Patent Text Reader

Abstract

The present application discloses a supported catalyst, a preparation method thereof, and an application thereof in the direct low-temperature conversion of methane to acetic acid. The supported catalyst comprises an active component and a carrier; the active component is at least one of copper, nickel, chromium, and iron single atoms; the carrier is selected from at least one of molecular sieves and C3N4. The catalyst is applied to the direct low-temperature conversion of methane to acetic acid, which eliminates the intermediate steps in the existing acetic acid production process, saves costs, and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a supported catalyst and a preparation method thereof and application in direct low-temperature conversion of methane to produce acetic acid, belonging to the field of methane activation. Background Art

[0002] Acetic acid is a bulk chemical product and one of the most important organic acids. The global demand is about 20 million tons per year. It can be used to produce vinyl acetate, acetic anhydride, acetate and cellulose acetate. Compared with methanol, acetic acid is more difficult to be peroxidized to produce compounds such as CO2. The main methods for synthesizing acetic acid include fermentation of carbohydrates, oxidation of naphtha or n-butane, oxidation of ethylene or acetaldehyde and methanol carbonylation. Among them, methanol carbonylation accounts for 60% of the world's acetic acid production, that is, CH3OH+CO→CH3COOH. Monsanto uses rhodium as the main catalyst and iodide as the co-catalyst to produce acetic acid at 150-200°C and 3-6MPa, and the yield based on methanol can reach 99%. In 1996, BP of the United Kingdom launched the Cativa technology patent. The Cativa process uses a new catalyst system based on iridium and uses a variety of new additives, such as rhenium, ruthenium, osmium, etc. The iridium catalyst system is more active than the rhodium catalyst, has fewer by-products, and can be operated under low water concentration (less than 5%), which greatly improves the traditional methanol carbonylation process, reduces production costs by up to 30%, and saves 50% of expansion costs. In addition, due to the reduction in water concentration, CO utilization efficiency is improved and steam consumption is reduced. However, the current acetic acid production inevitably uses highly corrosive iodides and superacids, and requires expensive precious metal catalysts, which does not meet the future "green chemistry" production concept.

[0003] With the explosive growth of natural gas production in recent years, the research on efficient conversion of methane has attracted the attention of more and more researchers. At present, the most researched direction is the direct conversion of methane to methanol: In 2012, Hutchings' team used CuFe-ZSM-5 molecular sieve catalyst to achieve direct conversion of methane to methanol at 50°C (Angew. Chem. Int. Ed., 2012, 51, 5129-5133), but the research on direct conversion of methane to acetic acid is still in urgent need of development. The direct carbonylation of methane to acetic acid greatly reduces the production cost because it omits the intermediate processes such as the production of synthesis gas from methane and the further conversion of synthesis gas to methanol. It is considered to be the most promising direction for the production of acetic acid in the future. Since the reaction of preparing acetic acid from methane in one step involves multiple elementary steps such as: 1) activation of highly stable CH4 molecules; 2) CC coupling reaction; 3) hydrolysis reaction of methyl carbonyl group, it brings great challenges to the design of catalytic system. Early research on direct conversion of methane to acetic acid focused on homogeneous catalytic systems. Takahiro et al. (Chem. Lett., 1992, 1141-1142) used CuSO4 or Pd(OCOEt)2 as catalysts and K2S2O8 as oxidants at 80°C to achieve direct conversion of CH4 and CO to acetic acid. Lin et al. (Nature, 1994, 368, 613-615) replaced the oxidant with O2 and used RhCl3 as a catalyst to convert CH4 into acetic acid with high selectivity, with formic acid and methanol as byproducts. However, such catalysts are difficult to recycle, which severely limits their scale-up application. In 2017, the research group of Maria et al. (Nature, 2017, 551, 605-608) made a major breakthrough. They prepared a molecular sieve catalyst based on Rh single atoms, which achieved direct coupling of CH4 and CO in an oxygen atmosphere to prepare acetic acid, with the selectivity of acetic acid reaching 67% in the reaction. However, the reaction temperature of this process is still relatively high (150°C), and the CO utilization efficiency is reduced due to the oxidation of CO by oxygen during the reaction. In addition, the active component in the catalyst is the precious metal Rh, which has a relatively high cost. Until now, there are still various problems in the direct conversion of methane to acetic acid: low selectivity of the target product acetic acid, poor catalyst cycle stability, unclear reaction mechanism, etc. Therefore, the development of a single-atom catalytic system with low cost, high selectivity, high stability, and clear reaction route is the focus of current research. Summary of the invention

[0004] In order to overcome the problems in the prior art, the object of the present invention is to provide a method for directly converting methane into acetic acid at low temperature, which is simple and easy to operate, has low catalyst cost and is suitable for large-scale production.

[0005] To achieve the above object, in one aspect of the present application, a supported catalyst is provided, wherein the supported catalyst comprises an active component and a carrier;

[0006] The active group is a metal single atom, and the active component is selected from at least one of copper, nickel, chromium and iron;

[0007] The carrier is selected from at least one of molecular sieve and C3N4.

[0008] Optionally, in the supported catalyst, the content of the active component is 0.1 to 0.5% of the total mass of the catalyst, and the content of the active component is calculated based on the mass of a single metal atom;

[0009] The content of the carrier is 99.5-99.9% of the total mass of the supported catalyst.

[0010] Optionally, the molecular sieve is at least one of H-β, H-ZSM-5, and H-MOR molecular sieves;

[0011] The Si / Al ratio of the molecular sieve is 8-40.

[0012] Another aspect of the present application provides a method for preparing the above-mentioned supported catalyst, the preparation method comprising: loading the metal element on the carrier by an equal volume impregnation method to obtain a catalyst precursor, and performing calcination I, acid treatment, and calcination II to obtain the supported catalyst.

[0013] Through the equal volume impregnation method, a large amount of transition metal precursors are first allowed to enter the pores of the carrier or defect sites. A part of them forms single atoms, and the other part forms clusters or nanoparticles. Through acid washing, the easily removable metal clusters and nanoparticles are removed, and only the transition metal single atoms with strong interaction with the carrier are retained.

[0014] Optionally, the equal volume impregnation method comprises:

[0015] Adding a precursor solution containing active components into a molecular sieve, stirring and drying to obtain the catalyst precursor;

[0016] Optionally, the drying temperature is 60 to 150° C.; the drying time is 10 to 12 hours;

[0017] Optionally, the reduction conditions I are: calcination in air atmosphere, the calcination I temperature is 350°C to 550°C; the calcination I time is 3h to 5h; the flow rate of the air atmosphere is 20 to 30mL / min.

[0018] Optionally, the upper limit of the drying temperature can be independently selected from 100°C and 150°C; the lower limit can be independently selected from 60°C and 100°C;

[0019] Optionally, the upper limit of the drying time can be independently selected from 11h and 12h; the lower limit can be independently selected from 10h and 11h;

[0020] Optionally, the upper limit of the calcination temperature I can be independently selected from 450°C and 550°C; the lower limit can be independently selected from 350°C and 450°C;

[0021] Optionally, the upper limit of the calcination time I can be independently selected from 4h and 5h; the lower limit can be independently selected from 3h and 4h;

[0022] Optionally, the upper limit of the air atmosphere flow rate can be independently selected from 25 mL / min and 30 mL / min; the lower limit can be independently selected from 20 mL / min and 25 mL / min;

[0023] Optionally, the acid treatment includes: adding the calcined catalyst precursor to an acidic solution, heating, filtering, and drying;

[0024] Optionally, the concentration of the acidic solution is 0.1 to 0.5 mol / L;

[0025] Optionally, the upper limit of the concentration of the acidic solution can be independently selected from 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L; the lower limit can be independently selected from 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L;

[0026] Optionally, the mass volume ratio of the calcined catalyst precursor to the acidic solution is 1 g: 10 to 30 mL;

[0027] Optionally, the upper limit of the mass volume ratio of the reduced catalyst precursor to the acidic solution can be independently selected from 1g:10mL, 1g:20mL; the lower limit can be independently selected from 1g:20mL, 1g:30mL;

[0028] Optionally, the heating temperature is 60 to 80° C. and the heating time is 6 to 24 hours;

[0029] Optionally, the upper limit of the heating temperature can be independently selected from 70°C and 80°C; the lower limit can be independently selected from 60°C and 70°C;

[0030] Optionally, the upper limit of the heating time can be independently selected from 12h, 18h, 24h; the lower limit can be independently selected from 6h, 12h, 18h;

[0031] Optionally, the conditions for the calcination II are: calcination in an air atmosphere, the calcination II temperature is 350° C.; the calcination II time is 3 h to 5 h; and the flow rate of the air atmosphere is 20 to 30 mL / min.

[0032] Optionally, the upper limit of the calcination II time can be independently selected from 4h and 5h; the lower limit can be independently selected from 3h and 4h;

[0033] Optionally, the upper limit of the air atmosphere flow rate can be independently selected from 25 mL / min and 30 mL / min; the lower limit can be independently selected from 20 mL / min and 25 mL / min;

[0034] Optionally, the precursor solution containing the active component is selected from copper nitrate solution, nickel nitrate solution, chromium nitrate solution, and iron nitrate solution.

[0035] Optionally, the acidic solution is selected from at least one of oxalic acid, nitric acid or hydrochloric acid.

[0036] As a specific embodiment, the preparation method of the supported catalyst comprises:

[0037] S001. Preparation of supported catalyst precursor: Take a certain concentration of copper, nickel, chromium, and iron precursor solution, dilute with deionized water, and add dropwise to the molecular sieve or C3N4, stirring evenly. When the sample is in the form of viscous droplets, stop stirring, let it stand for 4 hours, put it in a vacuum drying oven, maintain vacuum drying at 60°C for 12 hours; obtain the catalyst precursor, and roast it at 350°C to 550°C under air purge for 3 hours, and the gas flow rate during the roasting process is 20 to 30 mL / min.

[0038] S002, acid treatment: add the reduced catalyst to an acid solution of 0.1-0.5 mol / L, and add 10-30 mL of acid solution per gram of catalyst. Heat to 80°C in a water bath, maintain for 6-24 hours, filter the treated sample, and dry it in a 150°C oven to obtain a precursor sample. Then roast it at 350°C-550°C under air purge for 3 hours, and the gas flow rate during the roasting process is 20-30 mL / min. The catalyst sample is obtained.

[0039] In another aspect of the present application, a method for preparing acetic acid by converting methane is provided, the method comprising:

[0040] A raw material containing CH4 and CO is contacted with an aqueous solution containing a catalyst and an oxidant to react to obtain acetic acid;

[0041] Wherein, the catalyst is selected from the above-mentioned supported catalyst or the supported catalyst obtained according to the above-mentioned preparation method.

[0042] Optionally, in the raw material, the volume fraction of CH4 is 50% to 90%, and the volume fraction of CO is 10% to 50%;

[0043] Optionally, the oxidant is selected from at least one of H2O2 and K2S2O8;

[0044] Optionally, in the aqueous solution containing the catalyst and the oxidant, the concentration of the oxidant is 0.1 to 0.5 mol / L;

[0045] Optionally, the upper limit of the concentration of the oxidant can be independently selected from 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L; the lower limit can be independently selected from 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L;

[0046] Optionally, the content of the catalyst is 10 to 50 mg;

[0047] Optionally, the reaction pressure is 2-4 MPa, the reaction temperature is 20-70° C., and the reaction time is 0.5-10 h;

[0048] Preferably, the reaction temperature is 25 to 30°C;

[0049] Optionally, the upper limit of the reaction pressure can be independently selected from 3MPa and 4MPa; the lower limit can be independently selected from 2MPa and 3MPa.

[0050] Optionally, the upper limit of the reaction temperature can be independently selected from 30°C, 40°C, 50°C, 60°C, and 70°C; the lower limit can be independently selected from 20°C, 30°C, 40°C, 50°C, and 60°C.

[0051] Optionally, the reaction is carried out in a batch reactor.

[0052] As a specific embodiment, the method for producing acetic acid by direct low-temperature conversion of methane includes: using a transition metal single-atom catalyst uniformly dispersed in an aqueous solution containing an oxidant, introducing CH4 and CO at a certain pressure, reacting at a certain temperature, and being able to generate acetic acid with high selectivity.

[0053] A transition metal single atom catalyst is added to a 0.1-0.5 mol / L aqueous oxidant solution and ultrasonicated, and then placed in a high-pressure reactor. A mixed gas consisting of CO and CH4 is introduced into the reactor. The total pressure is 2-4 MPa, the reaction temperature is 20-70°C, and the reaction time is 0.5-10 h.

[0054] The added CO gas not only serves as a raw material for acetic acid, but also can promote the activation rate of methane.

[0055] A supported transition metal catalyst was prepared by an equal volume impregnation method, and then treated with different acidic solutions such as oxalic acid to remove excess metal nanoparticles and retain single atoms, thereby obtaining a series of transition metal single atom catalysts. The transition metal single atom catalyst was mixed with a low concentration of an oxidant aqueous solution and added to a reactor, and a certain pressure of CH4 and CO were introduced to react at room temperature, and acetic acid could be generated with high selectivity. In the catalyst of the present invention, the mass content of the transition metal single atom is 0.1 to 0.5%.

[0056] The beneficial effects of this application include:

[0057] 1) The present invention conveniently prepares a highly stable transition metal single atom catalyst by acid treatment, replacing the noble metal nanocatalyst to reduce the cost. In addition, hydrogen peroxide is preferentially selected as the oxidant, replacing the corrosive superacid and molecular oxygen that reacts only at high temperature, which conforms to the concept of "green chemistry".

[0058] 2) The present invention reduces the reaction temperature to room temperature while ensuring the reaction performance, thereby reducing the reaction energy consumption and further reducing the cost. At the same time, CO is added not only as a reactant, but also can be used to modify the active sites of the catalyst, thereby increasing the activation rate and selectivity of the catalyst for methane, and further increasing the conversion rate of methane.

[0059] 3) The present invention makes the selectivity of acetic acid reach more than 90% by utilizing the combination of single atoms of different elements on the carrier. DETAILED DESCRIPTION

[0060] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0061] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.

[0062] The analysis method in the examples of this application is as follows:

[0063] The selectivity of liquid oxygenates is calculated as follows:

[0064] Product selectivity = {the amount of acetic acid / (the total amount of methane-the amount of remaining methane)}×100%

[0065] The TOF value of the catalyst is calculated as follows:

[0066] TOF = amount of acetic acid / amount of active metal / reaction time

[0067] Embodiment 1:

[0068] Preparation of Fe / ZSM-5, Fe / β, and Fe / MOR single-atom catalysts with a loading of 0.1wt.%

[0069] Place 1g of H-ZSM-5 zeolite molecular sieve carrier with Si / Al of 15 in a beaker, take 1mL of 0.1mol / L ferric nitrate solution, add it dropwise to the zeolite molecular sieve, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 500℃ in an air atmosphere for 3h to obtain a Fe / ZSM-5 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. Place 1g of the calcined Fe / ZSM-5 catalyst in a beaker, add 30mL of 0.3mol / L oxalic acid solution, and stir it in a water bath at 80℃ for 24h. Filter the acid-treated sample, dry it at 150℃, calcine it at 350℃ in an air atmosphere for 3h, and obtain a 0.1wt.% Fe / ZSM-5 single atom catalyst after natural cooling. The iron loading in the catalyst was determined by ICP-OES characterization.

[0070] The carriers were replaced with H-β type and H-MOR type zeolite molecular sieves with Si / Al of 15 and Si / Al of 15, respectively, and prepared according to the above conditions to obtain catalysts with loading amounts of 0.1wt.% Fe / β and 0.1wt.% Fe / MOR.

[0071] The carriers were replaced with H-ZSM-5 type with Si / Al of 9, H-β type with Si / Al of 20 and H-MOR type zeolite molecular sieves with Si / Al of 40, and prepared according to the above conditions to obtain 0.1wt.% Fe / ZSM-5, 0.1wt.% Fe / β and 0.1wt.% Fe / MOR catalysts with different Si / Al.

[0072] Embodiment 2:

[0073] Preparation of 0.1wt.% Fe / C3N4 catalyst

[0074] Place 1g of C3N4 carrier in a beaker, take 1mL of 0.1mol / L ferric nitrate solution, add it dropwise to C3N4, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 350℃ for 3h in an air atmosphere to obtain a Fe / C3N4 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. The calcined 1g Fe / C3N4 catalyst was placed in a beaker, 10mL of 0.1mol / L oxalic acid solution was added, and stirred at room temperature for 12h. The acid-treated sample was filtered, dried at 150℃, calcined at 350℃ for 3h in an air atmosphere, and a 0.1wt.% Fe / C3N4 single atom catalyst was obtained after natural cooling. The iron loading in the catalyst was determined by ICP-OES characterization.

[0075] Embodiment 3:

[0076] Preparation of Cu / ZSM-5, Cu / β, and Cu / MOR single-atom catalysts with a loading of 0.1wt.%

[0077] Place 1g of H-ZSM-5 zeolite molecular sieve carrier with Si / Al of 15 in a beaker, take 1mL of copper nitrate solution with a concentration of 0.1mol / L, add it dropwise to the zeolite molecular sieve, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst is calcined at 350℃ in an air atmosphere for 3h to obtain a Cu / ZSM-5 supported catalyst. The air flow rate is 25mL / min. The heating rate is 2℃ / min. Place 1g of the calcined Cu / ZSM-5 catalyst in a beaker, add 30mL of oxalic acid solution with a concentration of 0.3mol / L, and stir it in a water bath at 80℃ for 24h. Filter the acid-treated sample, dry it at 150℃, calcine it at 350℃ in an air atmosphere for 3h, and obtain a 0.1wt.% Cu / ZSM-5 single atom catalyst after natural cooling. The copper loading in the catalyst was determined by ICP-OES characterization.

[0078] The carriers were replaced with H-β type and H-MOR type zeolite molecular sieves with Si / Al of 15 and Si / Al of 15, respectively, and prepared according to the above conditions to obtain catalysts with loading amounts of 0.1wt.% Cu / β and 0.1wt.% Cu / MOR.

[0079] The carriers were replaced with H-ZSM-5 type with Si / Al of 9, H-β type with Si / Al of 20 and H-MOR type zeolite molecular sieves with Si / Al of 40, and prepared according to the above conditions to obtain 0.1wt.% Cu / ZSM-5, 0.1wt.% Cu / β and 0.1wt.% Cu / MOR catalysts with different Si / Al.

[0080] Embodiment 4:

[0081] Preparation of 0.1wt.% Cu / C3N4 catalyst

[0082] Place 1g of C3N4 carrier in a beaker, take 1mL of 0.1mol / L copper nitrate solution, add it dropwise to C3N4, stir evenly until the sample becomes a viscous liquid, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 350℃ for 3h in an air atmosphere to obtain a Cu / C3N4 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. The calcined 1g Cu / C3N4 catalyst was placed in a beaker, 10mL of 0.1mol / L oxalic acid solution was added, and stirred at room temperature for 12h. The acid-treated sample was filtered, dried at 150℃, calcined at 350℃ for 3h in an air atmosphere, and a 0.1wt.% Cu / C3N4 single atom catalyst was obtained after natural cooling. The copper loading in the catalyst was determined by ICP-OES characterization.

[0083] Embodiment 5:

[0084] Preparation of Ni / ZSM-5, Ni / β, and Ni / MOR single-atom catalysts with a loading of 0.1wt.%

[0085] Place 1g of H-ZSM-5 zeolite molecular sieve carrier with Si / Al of 15 in a beaker, take 1mL of nickel nitrate solution with a concentration of 0.1mol / L, add it dropwise to the zeolite molecular sieve, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst is calcined at 500℃ in an air atmosphere for 3h to obtain a Ni / ZSM-5 supported catalyst. The air flow rate is 25mL / min. The heating rate is 2℃ / min. Place 1g of Ni / ZSM-5 catalyst after calcination in a beaker, add 30mL of oxalic acid solution with a concentration of 0.2mol / L, and stir it in a water bath at 80℃ for 24h. Filter the acid-treated sample, dry it at 150℃, calcine it at 350℃ in an air atmosphere for 3h, and obtain a 0.1wt.% Ni / ZSM-5 single atom catalyst after natural cooling. The nickel loading in the catalyst was determined by ICP-OES characterization.

[0086] The carriers were replaced with H-β type and H-MOR type zeolite molecular sieves with Si / Al of 15 and Si / Al of 15, respectively, and prepared according to the above conditions to obtain catalysts with loading amounts of 0.1wt.% Ni / β and 0.1wt.% Ni / MOR.

[0087] The carriers were replaced with H-ZSM-5 zeolite molecular sieves with Si / Al of 9, H-β zeolite molecular sieves with Si / Al of 20, and H-MOR zeolite molecular sieves with Si / Al of 40, respectively, and prepared according to the above conditions to obtain 0.1wt.% Ni / ZSM-5, 0.1wt.% Ni / β and 0.1wt.% Ni / MOR catalysts with different Si / Al.

[0088] Embodiment 6:

[0089] Preparation of 0.1wt.% Ni / C3N4 catalyst

[0090] Place 1g of C3N4 carrier in a beaker, take 1mL of 0.1mol / L nickel nitrate solution, add it dropwise to C3N4, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 350℃ for 3h in an air atmosphere to obtain a Ni / C3N4 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. The calcined 1g Ni / C3N4 catalyst was placed in a beaker, 10mL of 0.1mol / L oxalic acid solution was added, and stirred at room temperature for 12h. The acid-treated sample was filtered, dried at 150℃, calcined at 350℃ for 3h in an air atmosphere, and a 0.1wt.% Ni / C3N4 single atom catalyst was obtained after natural cooling. The nickel loading in the catalyst was determined by ICP-OES characterization.

[0091] Embodiment 7:

[0092] Preparation of 0.1wt.% Cr / ZSM-5, Cr / β, and Cr / MOR single-atom catalysts

[0093] Place 1g of H-ZSM-5 zeolite molecular sieve carrier with Si / Al of 15 in a beaker, take 1mL of 0.1mol / L chromium nitrate solution, add it dropwise to the zeolite molecular sieve, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 500℃ in an air atmosphere for 3h to obtain a Cr / ZSM-5 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. The calcined 1gCr / ZSM-5 catalyst was placed in a beaker, 20mL of 0.2mol / L oxalic acid solution was added, and stirred in a water bath at 80℃ for 24h. The acid-treated sample was filtered, dried at 150℃, calcined at 350℃ in an air atmosphere for 3h, and a 0.1wt.%Cr / ZSM-5 single atom catalyst was obtained after natural cooling. The chromium loading in the catalyst was determined by ICP-OES characterization.

[0094] The carriers were replaced with H-β type and H-MOR type zeolite molecular sieves with Si / Al of 15 and Si / Al of 15, respectively, and prepared according to the above conditions to obtain catalysts with loading amounts of 0.1wt.% Cr / β and 0.1wt.% Cr / MOR.

[0095] The carriers were replaced with H-ZSM-5 type with Si / Al of 9, H-β type with Si / Al of 20 and H-MOR type zeolite molecular sieves with Si / Al of 40, and prepared according to the above conditions to obtain 0.1wt.% Cr / ZSM-5, 0.1wt.% Cr / β and 0.1wt.% Cr / MOR catalysts with different Si / Al.

[0096] Embodiment 8:

[0097] Preparation of 0.1wt.% Cr / C3N4 catalyst

[0098] Place 1g of C3N4 carrier in a beaker, take 1mL of 0.1mol / L chromium nitrate solution, add it dropwise to C3N4, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst is calcined at 350℃ in an air atmosphere for 3h to obtain a Cr / C3N4 supported catalyst. The air flow rate is 25mL / min. The heating rate is 2℃ / min. Place 1g of calcined Cr / C3N4 catalyst in a beaker, add 10mL of 0.1mol / L oxalic acid solution, and stir at room temperature for 12h. Filter the acid-treated sample, dry it at 150℃, calcine it at 350℃ in an air atmosphere for 3h, and obtain a 0.1wt.% Cr / C3N4 single atom catalyst after natural cooling. The chromium loading in the catalyst is determined by ICP-OES characterization.

[0099] Embodiment 9:

[0100] Preparation of 0.2wt.% FeCu / C3N4 catalyst

[0101] Place 1g of C3N4 carrier in a beaker, take 0.5mL of 0.1mol / L copper nitrate solution and 0.5mL of 0.1mol / L ferric nitrate solution, mix them evenly and add them dropwise to C3N4. Stir evenly until the sample becomes a viscous droplet, then stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst was calcined at 350℃ in an air atmosphere for 3h to obtain a FeCu / C3N4 supported catalyst. The air flow rate was 25mL / min. The heating rate was 2℃ / min. The calcined 1g FeCu / C3N4 catalyst was placed in a beaker, 10mL of 0.1mol / L oxalic acid solution was added, and stirred at room temperature for 12h. The acid-treated sample was filtered, dried at 150℃, calcined at 350℃ in an air atmosphere for 3h, and a 0.2wt% FeCu / C3N4 single atom catalyst was obtained after natural cooling. The iron and copper loadings in the catalyst were determined by ICP-OES characterization, wherein the Fe loading was 0.1 wt.%, and the Cu loading was 0.1 wt.%.

[0102] Example 10

[0103] The calcination temperature I of the method for preparing 0.1wt.% Fe / ZSM-5 with Si / Al ratio of 15 in Example 1 was changed to 350°C, 450°C, and 550°C, while other conditions remained unchanged, to obtain 0.1wt.% Fe / ZSM-5 catalysts with different calcination temperatures, which were marked as 0.1wt.% Fe / ZSM-5-350, 0.1wt.% Fe / ZSM-5-450, and 0.1wt.% Fe / ZSM-5-550, respectively.

[0104] Embodiment 11

[0105] Preparation of 0.2wt.% Fe / ZSM-5 Catalyst

[0106] Place 1g H-ZSM-5 (Si / Al is 15) zeolite molecular sieve carrier in a beaker, take 1mL of 0.1mol / L ferric nitrate solution, add it dropwise to the zeolite molecular sieve, stir evenly until the sample becomes viscous, and stop stirring. After standing for 4h, put it in a vacuum drying oven and dry it at 60℃ vacuum conditions for 12h. After drying, the catalyst is calcined at 500℃ in an air atmosphere for 3h to obtain a Fe / ZSM-5 supported catalyst. The air flow rate is 25mL / min. The heating rate is 2℃ / min. Place 1g of the calcined Fe / ZSM-5 catalyst in a beaker, add 20mL of 0.2mol / L oxalic acid solution, and stir it in a 70℃ water bath for 12h. Filter the acid-treated sample, dry it at 150℃, calcine it at 350℃ in an air atmosphere for 3h, and obtain a 0.2wt.% Fe / ZSM-5 single atom catalyst after natural cooling. The iron loading in the catalyst was determined by ICP-OES characterization.

[0107] By changing the oxalic acid concentration in the above preparation method to 0.1 mol / L, the water bath temperature to 60°C, and the stirring time to 6 h, a Fe / ZSM-5 with a loading of 0.3 wt.% can be obtained.

[0108] Embodiment 12:

[0109] Take the study on catalytic conversion of methane to acetic acid using 0.1wt.% Fe / ZSM-5 catalyst obtained in Example 1 as an example:

[0110] The catalyst's direct methane conversion to oxygen-containing compounds reaction performance was evaluated using an intermittent high-pressure reactor. 20 mg of 0.1 wt.% Fe / ZSM-5 catalyst was added to 10 mL of 0.3 mol / L aqueous hydrogen peroxide solution, followed by ultrasonic treatment for 5 min. 20 bar CH4 and 10 bar CO were added to the reaction vessel. The reactor was placed in a heating furnace and maintained at room temperature at 25 °C for 1 h. The solution was continuously stirred with a magnetic cross rotor during the reaction. After the reaction was completed, the reactor was cooled with ice water. When the solution temperature was below 10 °C, a gas chromatograph was used to analyze the gas composition. The reaction liquid after filtering the catalyst was collected and the amount of oxygen-containing compounds in the liquid was quantified by nuclear magnetic resonance (NMR) measurement. The selectivity of liquid-phase oxygen-containing compounds and the TOF value of the catalyst were calculated.

[0111] Table 1 Selectivity of liquid oxygen-containing compounds and TOF value of catalyst 0.1wt.% Fe / ZSM-5 in H2O2 aqueous solution

[0112]

[0113] As shown in the table, the selectivity of acetic acid reached 95% and the TOF reached 138h -1 , the conversion efficiency is higher.

[0114] Embodiment 13:

[0115] Study on the reaction performance of methane conversion to acetic acid by different oxidants:

[0116] According to the method shown in Example 12, the 0.1wt.% Fe / ZSM-5 catalyst obtained in Example 1 was used, and the aqueous hydrogen peroxide solution was replaced with a 0.3mol / L K2S2O8 aqueous solution to compare the changes in reaction performance:

[0117] Table 2 Selectivity and TOF value of liquid oxygen-containing compounds in K2S2O8 aqueous solution over catalyst 0.1wt.% Fe / ZSM-5

[0118]

[0119]

[0120] As shown in the table, the selectivity of acetic acid reached 90% and the TOF reached 76h -1 The conversion efficiency is not as good as that of the system with hydrogen peroxide as the oxidant.

[0121] Embodiment 14:

[0122] Study on the performance of methane conversion to acetic acid over the same loading of M-zeolite catalyst:

[0123] According to the method shown in Example 12, 0.1 wt.% Cu / ZSM-5 catalyst prepared in Example 3, 0.1 wt.% Ni / ZSM-5 catalyst prepared in Example 5, 0.1 wt.% Cr / ZSM-5 catalyst prepared in Example 7, and 0.1 wt.% Fe / ZSM-5 catalyst prepared in Example 1 were used to catalyze methane conversion to produce acetic acid, and the changes in the methane activation ability of the same loading of M-molecular sieve single atom catalysts were compared, as shown in Table 3.

[0124] Table 3 Comparison of catalyst performance of different metals loaded on H-ZSM-5

[0125]

[0126] As can be seen from the table, the selectivity of methane conversion to acetic acid with Cu, Ni, Cr, and Fe single atoms loaded on H-ZSM-5 is above 80%, among which 0.1wt.% Fe / ZSM-5 has the best performance.

[0127] Embodiment 15:

[0128] Comparison of reaction performance of M single atom catalysts loaded on different carriers:

[0129] According to the method shown in Example 12, the M single atom catalysts loaded on different carriers were replaced, including the 0.1wt.% Cu / C3N4 catalyst obtained in Example 4, the 0.1wt.% Cu / ZSM-5 catalyst obtained in Example 3, the 0.1wt.% Ni / C3N4 catalyst obtained in Example 6, the 0.1wt.% Ni / ZSM-5 catalyst obtained in Example 5, the 0.1wt.% Cr / C3N4 catalyst obtained in Example 8, the 0.1wt.% Cr / ZSM-5 catalyst obtained in Example 7, the 0.1wt.% Fe / C3N4 catalyst obtained in Example 2, and the 0.1wt.% Fe / ZSM-5 catalyst obtained in Example 1; the catalytic performance was compared, as shown in Table 4.

[0130] Table 4 Comparison of performance of M single atom catalysts supported on different supports

[0131]

[0132] It can be seen from the table that, except for Fe, the M single atom catalyst supported on the C3N4 carrier has better selectivity, but the M single atom catalyst supported on the molecular sieve has higher reaction activity.

[0133] Embodiment 16:

[0134] The performance comparison of the catalysts loaded with Fe and Cu single atoms separately and loaded with Fe and Cu single atoms simultaneously is shown in Table 5:

[0135] According to the method shown in Example 12, the 0.1wt.% Fe / C3N4 catalyst prepared in Example 2, the 0.1wt.% Cu / C3N4 catalyst prepared in Example 4, and the 0.2wt.% FeCu / C3N4 catalyst prepared in Example 9 were used to catalyze the conversion of methane to acetic acid, and the changes in the methane activation ability of the catalysts loaded with Fe and Cu single atoms alone and loaded with Fe and Cu single atoms simultaneously were compared.

[0136] Table 5 Comparison of catalyst performance of 0.1wt.%Fe / C3N4, 0.1wt.%Cu / C3N4 and 0.2wt.%FeCu / C3N4

[0137]

[0138] It can be seen from the table that the catalyst performance of the carrier with Fe and Cu single atoms loaded simultaneously is better than that of the catalyst with Fe and Cu loaded separately.

[0139] Example 17:

[0140] Evaluation of reaction stability of M / ZSM-5 single atom catalyst:

[0141] The catalyst after the reaction was evaluated four times using the performance evaluation method for catalytic methane conversion to acetic acid described in Example 12. The catalyst after the reaction was filtered, washed, dried at 60°C and reused. Taking the 0.1wt.% Fe / ZSM-5 prepared in Example 1 as an example:

[0142] Table 6 Cyclic stability of 0.1wt.% Fe / ZSM-5 single atom catalyst

[0143]

[0144] From the data in Table 6, it can be seen that 0.1wt.% Fe / ZSM-5 can still maintain 93.4% acetic acid selectivity after five reaction cycles, and the reaction activity remains basically unchanged, with good cycle stability.

[0145] Embodiment 18:

[0146] Evaluation of catalytic performance of Fe-ZSM-5 single atom catalyst under different reaction conditions:

[0147] Table 7 shows the catalytic performance comparison of the 0.1wt% Fe-ZSM-5 single atom catalyst prepared using Example 1 under different reaction conditions:

[0148] Table 7 Comparison of catalyst performance of Fe-ZSM-5 under different reaction conditions

[0149]

[0150] As shown in Table 7, Fe-ZSM-5 did not generate any product at 150°C with oxygen as the oxidant. At room temperature, no acetic acid was generated in the absence of H2O2 or CO. Moreover, the addition of CO increased the conversion of methane by an order of magnitude, proving the beneficial effect of CO on the catalytic system.

[0151] Embodiment 19:

[0152] Comparison of performance of Fe single atom catalysts at different reaction temperatures:

[0153] According to the method shown in Example 12, the reaction temperature was changed to 50°C and 70°C respectively, and the 0.1wt.% Fe / ZSM-5 catalyst prepared in Example 1 was used to catalyze methane conversion to produce acetic acid, and the performance changes of the Fe single atom catalyst at different reaction temperatures were compared.

[0154] Table 8 Comparison of performance of 0.1wt.% Fe / ZSM-5 catalyst at different reaction temperatures

[0155]

[0156]

[0157] As shown in the data in Table 8, with the increase of temperature, the reaction activity of the 0.1 wt.% Fe / ZSM-5 catalyst gradually increased, but the selectivity of acetic acid gradually decreased.

[0158] Embodiment 20:

[0159] Comparison of the performance of Fe / ZSM-5 catalysts with different iron loadings in catalytic conversion of methane to acetic acid:

[0160] According to the method shown in Example 12, the 0.1wt.% Fe / ZSM-5 prepared in Example 1 and the 0.2wt.% Fe / ZSM-5 and 0.3wt.% Fe / ZSM-5 catalysts prepared in Example 1 were used to catalyze the conversion of methane to acetic acid, and the reaction performances of Fe / ZSM-5 catalysts with different loadings were compared.

[0161] Table 9 Comparison of performance of Fe / ZSM-5 catalysts with different iron loadings in catalytic methane conversion to acetic acid

[0162]

[0163] As shown in Table 9, with the increase of Fe loading, the yield of acetic acid also increased accordingly, and the acetic acid selectivity remained basically unchanged.

[0164] Embodiment 21:

[0165] Effect of different calcination temperatures on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid:

[0166] According to the method shown in Example 12, 0.1wt.% Fe / ZSM-5-350, 0.1wt.% Fe / ZSM-5-450, and 0.1wt.% Fe / ZSM-5-550 catalysts prepared in Example 10 were used to catalyze methane conversion to produce acetic acid, and the effects of different calcination temperatures on the performance of Fe / ZSM-5 catalysts in catalyzing methane conversion to produce acetic acid were compared.

[0167] Table 10 Comparison of the performance of Fe / ZSM-5 catalysts catalyzing methane conversion to acetic acid at different calcination temperatures

[0168]

[0169]

[0170] As shown in Table 10, when the Fe calcination temperature increased to 550 °C, the selectivity of acetic acid decreased to 85.2%, which may be because the excessively high calcination temperature would cause the agglomeration of Fe single atoms.

[0171] Embodiment 22:

[0172] Effect of different hydrogen peroxide concentrations on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid:

[0173] According to the method shown in Example 12, the concentration of hydrogen peroxide was changed to 0.1 mol / L, 0.3 mol / L, and 0.5 mol / L, respectively. The 0.1 wt.% Fe / ZSM-5 catalyst prepared in Example 1 was used to catalyze the conversion of methane to acetic acid, and the effects of different hydrogen peroxide concentrations on the performance of the Fe / ZSM-5 catalyst for catalyzing the conversion of methane to acetic acid were compared.

[0174] Table 11 Effect of different hydrogen peroxide concentrations on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid

[0175]

[0176] As shown in Table 11, as the concentration of hydrogen peroxide increases, the yield of acetic acid increases accordingly, but the selectivity of acetic acid decreases slightly.

[0177] Embodiment 23:

[0178] Effects of different reaction times on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid:

[0179] According to the method shown in Example 12, the reaction time was changed to 0.5h, 1h, 2h, and 5h, respectively. The 0.1wt.% Fe / ZSM-5 catalyst prepared in Example 1 was used to catalyze the conversion of methane to acetic acid, and the effects of different reaction times on the performance of the Fe / ZSM-5 catalyst in catalyzing the conversion of methane to acetic acid were compared.

[0180] Table 12 Effect of different reaction times on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid

[0181]

[0182] Embodiment 24:

[0183] Effect of different methane partial pressures on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid:

[0184] According to the method shown in Example 12, the methane partial pressure was changed to 10 bar, 20 bar, and 30 bar respectively, and the 0.1 wt.% Fe / ZSM-5 catalyst prepared in Example 1 was used to catalyze the conversion of methane to acetic acid, and the effects of different methane partial pressures on the performance of the Fe / ZSM-5 catalyst in catalyzing the conversion of methane to acetic acid were compared.

[0185] Table 13 Effect of different methane partial pressures on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid

[0186]

[0187] As shown in Table 13, as the methane partial pressure increases, the total amount of products increases accordingly, but the selectivity of acetic acid decreases slightly.

[0188] Embodiment 25:

[0189] Effect of different CO partial pressures on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid:

[0190] According to the method shown in Example 12, the CO partial pressure was changed to 5 bar, 10 bar, and 20 bar respectively, and the 0.1 wt.% Fe / ZSM-5 catalyst prepared in Example 1 was used to catalyze the conversion of methane to acetic acid, and the effects of different methane partial pressures on the performance of the Fe / ZSM-5 catalyst in catalyzing the conversion of methane to acetic acid were compared.

[0191] Table 14 Effect of different CO partial pressures on the performance of Fe / ZSM-5 catalyst for methane conversion to acetic acid

[0192]

[0193] As shown in Table 14, with the increase of CO partial pressure, the yield and selectivity of the product did not change much.

[0194] Embodiment 26:

[0195] Effect of different Si / Al H-ZSM-5 supports on the performance of Fe single atom catalysts for methane conversion to acetic acid:

[0196] According to the method shown in Example 12, the 0.1wt.% Fe / ZSM-5 catalyst with Si / Al of 9, 15, 20, and 40 prepared in Example 1 was used to catalyze the conversion of methane to acetic acid, and the effects of H-ZSM-5 carriers with different Si / Al on the performance of Fe single-atom catalysts for catalyzing the conversion of methane to acetic acid were compared.

[0197] Table 15 Effect of H-ZSM-5 supports with different Si / Al content on the performance of Fe single atom catalysts for methane conversion to acetic acid

[0198]

[0199] As shown in Table 15, as the Si / Al ratio of the carrier increases, the total amount of product does not change much, but the selectivity of acetic acid gradually decreases.

[0200] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing acetic acid by converting methane, characterized in that: A raw material containing CH4 and CO is contacted with an aqueous solution containing a supported catalyst and an oxidant to react to obtain acetic acid; The supported catalyst comprises an active component and a carrier; The active component is at least one of copper, nickel, chromium and iron single atoms; The carrier is selected from at least one of molecular sieve and C3N4; In the supported catalyst, the content of the active component is 0.1-0.5% of the total mass of the catalyst, and the content of the active component is calculated based on the mass of a single transition metal atom; The content of the carrier is 99.5-99.9% of the total mass of the supported catalyst; The molecular sieve is at least one of H-β, H-ZSM-5 and H-MOR molecular sieves; The Si / Al ratio of the molecular sieve is 8 to 40; The oxidant is selected from at least one of H2O2 and K2S2O8; The metal element is loaded on the carrier by an equal volume impregnation method to obtain a catalyst precursor, and then calcined I, acid treated, and calcined II to obtain the supported catalyst; The calcination I and calcination II are carried out in an air atmosphere.

2. The method according to claim 1, characterized in that The equal volume impregnation method comprises: Adding a precursor solution containing active components into a molecular sieve, stirring and drying to obtain the catalyst precursor; The drying temperature is 60-150°C; the drying time is 10-12 h; The conditions of the calcination I are as follows: the calcination I temperature is 350° C. to 550° C.; the calcination I time is 3 h to 5 h; and the flow rate of the air atmosphere is 20 to 30 mL / min.

3. The method according to claim 1, characterized in that The acid treatment comprises: adding the calcined catalyst precursor into an acidic solution, heating, filtering, and drying; The concentration of the acidic solution is 0.1-0.5 mol / L; The mass volume ratio of the reduced catalyst precursor to the acidic solution is 1 g: 10-30 mL; The heating temperature is 60-80°C; the heating time is 6-24h; The conditions of the calcination II are as follows: the calcination II temperature is 350° C.; the calcination II time is 3 h to 5 h; and the flow rate of the air atmosphere is 20 to 30 mL / min.

4. The method according to claim 2, characterized in that: The precursor solution containing active components is selected from copper nitrate solution, nickel nitrate solution, chromium nitrate solution and iron nitrate solution.

5. The method according to claim 3, characterized in that: The acidic solution is selected from at least one of oxalic acid, nitric acid or hydrochloric acid.

6. The method according to claim 1, characterized in that In the raw material, the volume fraction of CH4 is 50% to 90%, and the volume fraction of CO is 10% to 50%; In the aqueous solution containing the catalyst and the oxidant, the concentration of the oxidant is 0.1-0.5 mol / L; The content of the catalyst is 10-50 mg; The reaction pressure is 2-4 MPa, the reaction temperature is 20-70°C, and the reaction time is 0.5-10 h; The reaction is carried out in a batch reactor.

Citation Information

Patent Citations

  • Selective oxidation of hydrocarbons using heterogeneous catalysts

    CN103476737A

  • Preparation method and application of HZSM-5 molecular sieve catalyst modified by nickel and chromium

    CN108043450A

  • Supported catalyst, preparation method and application thereof

    CN112774709A